Gestion por procesos del sistema de recoleccion selectiva y su incidencia en el manejo de residuos solidos del departamento de salud e higiene del gobierno autonomo descentralizado del canton Mocache, año 2014. - Mendoza Figueroa, Jacinto Carlos (2016)
This work was done in the Mocache Canton, belonging to the province of Los Rios, to determine the amount and type of solid waste generated for the current situation of their management and sustainable management of solid waste recyclable improve the quality of life and environment for communities in the Canton with the formation of micro Community recycling and reuse of organic and inorganic solid waste as a sustainable and viable alternative within the Mocache Canton. In the Canton Mocache, the per capita production of solid waste is 0.55 kg / person / day approximately, which is estimated at a daily production of 12.21 tons / day of solid wastes, organic wastes 31.05 % 48.56%; 17.24% paper, cardboard 12.26%; Plastic 33.72%; Aluminum 0.78%; Glass bottles with 3.88% and 1.86% Other. An appropriate mechanism for recycling and reuse of organic and inorganic solid waste prolong the life of the dump to 6,039 tons / day, prolonging the lifetime of the dump of Mocache Canton, generating significant revenue which may be between 120 to $ 260,000 annually, money that will be aimed at the sustainability of microenterprises recycling and sustainability of those who conform only, thus improving the quality of life and environment of people. Keywords: Solid waste company, Recycling, Sustainability